Three-dimensional assessment of facial asymmetry in preschool patients with orofacial clefts after neonatal cheiloplasty - Moslerová, Veronika; Dadáková, Martina; Dupej, Ján; Hoffmannova, Eva; Borský, Jiří; Černý, Miloš; Bejda, Přemysl; Kočandrlová, Karolína; Velemínská, Jana (International journal of pediatric otorhinolaryngology, 2018)
OBJECTIVES: To evaluate facial asymmetry changes in pre-school patients with orofacial clefts after neonatal cheiloplasty and to compare facial asymmetry with age-matched healthy controls. METHODS AND MATERIALS: The sample consisted of patients with unilateral cleft lip (UCL), unilateral cleft lip and palate (UCLP), and bilateral cleft lip and palate (BCLP). The patients were divided in two age groups with a mean age of 3 years (n = 51) and 4.5 years (n = 45), respectively, and 78 age-matched individuals as controls. Three-dimensional (3D) facial scans were analyzed using geometric morphometry and multivariate statistics. RESULTS: Geometric morphometry showed positive deviations from perfect symmetry on the right side of the forehead in the intervention groups and the controls. The UCL groups showed the greatest asymmetric nasolabial area on the cleft-side labia and the contralateral nasal tip. The UCLP group showed, moreover, asymmetry in buccal region due to typical maxillar hypoplasia, which was accentuated in the older group. The BCLP groups showed slightly similar but greater asymmetry than the control groups, except for the philtrum region. CONCLUSIONS: Asymmetry of each of the cleft groups significantly differed from the controls. Except for the buccal region in the UCLP and BCLP groups, asymmetry did not significantly increase with age.
Keywords: 3D scanning; Cleft Palate; Neonatal cheiloplasty; Face; Facial Asymmetry; Female; Cleft Lip; Infant; Lip; Plastic Surgery Procedures; dítě; předškolní dítě; zobrazování trojrozměrné; novorozenec; Imaging, Three-Dimensional; ženské pohlaví; lidé; Infant, Newborn; rozštěp patra; zákroky plastické chirurgie; obličej; rozštěp rtu; Male; Cleft; kojenec; Child, Preschool; Asymmetry; Child; Geometric morphometry; mužské pohlaví; asymetrie obličeje; ret; Humans